The Implementation of Integrated Administration Services (PATEN) in Siak Regency, Riau - Kemal, Kemal (Research and Development Agency Ministry of Home Affairs, 2017)
This research is about the Implementation of District Integrated Administration Service (PATEN) in bringing closer and improving services to the community in Siak Regency, Riau Province. Law Number 23 of 2014 on Regional Government states that District Heads must implement two authorities, namely Attributive authority, and Delegated authority. The District head as, a regional apparatus, is no longer the head of a region that must obtain a delegation of some of the authority of the Regent/Mayor as stipulated by Regent/Mayor regulation. Not all Regents/Mayors delegate part of the authority to District Heads so that the implementation of service is centered in Regency/City. This research uses a descriptive qualitative method, and data collection technique is in the form of the interview, observation, and documentation. The results revealed that (1) PATEN in Siak District can bring closer and improve service to the community free of charge; (2) There is a strong commitment from the Siak Regent in the delegation of some of the licensing authority to the District Heads. For example, the presence of service space in the district with service counters, PATEN officers, the incentives of PATENT officers, and the direct supervision from the Regent. (3) Positive responses from the community, such as better service, free, and close to the service recipient community.